Investigation of Football Fans’ Betting Motivations and Love-Hate Relationship - Kural, Sercan; Özbek, Oğuz (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2025)
The success or failure of sports clubs is among the issues that are given great importance among the fans. Fans can feel proud and happy when their team wins and unhappy when they lose. The happiness of the fans can appear in the form of love towards their own team and hatred towards the opposing team. However, the feelings of love and hate of the fans may be related to betting games. In this context, it was aimed to test the relationship between the love-hate levels of football fans and their motivation to gamling. The study group of the research consists of 261 football fans. In the selection of the study group, the convenience sampling method, one of the purposive sampling approaches, was used. “Gambling Motivation Scale” and “Fan LoveHate Scale” were used as data collection tools in the study. In the analysis of the data obtained, t-test for independent samples, ANOVA and correlation analysis methods were used. Cronbach’s Alpha analysis method was used to test the reliability of both scales for the research group. When the comparison results regarding gender were examined, no significant difference was found within the scope of the supporter love hate scale. When the sub-dimensions of the betting motivation scale were examined, a significant difference was found in all sub-dimensions, except for only the sub-dimension of “Extrinsic motivation-inrojected”. In addition, when ANOVA analysis was analyzed according to the variable of gamling, a significant difference was found in all sub-dimensions of the GMS and in the love sub-dimension of the FLHS. Finally, as a result of pearson correlation analysis, it was determined that there was a positive relationship between the love and hate levels of the fans and their motivation to bet. As a result, it can be said that fans’ love-hate emotion levels may have an effect on their motivation to gamling.